Primerjava učinkovitosti različnih pragov izgube hitrosti med vadbo proti uporu za izboljšanje mišične zmogljivosti - Kožuh, Martin (Šport (Ljubljana), 2022)
Velocity based training is a novel method for control and optimization of training. Velocity loss during resistance training is a difference between the fastest and the ongoing repetition. It is an indicator of neuro-muscular fatigue. Excessiv fatigue has a negative influence on developing strength, power and speed, which means that monitoring fatigue by measuring velocity of repetition is a useful method for training optimization. To use this method, we first choose desired velocity loss threshold (measured in % of velocity loss compared to fastest repetition) and the set is finished, when athlete reaches that threshold, no matter how many repetitions he completed. We conducted a meta-analysis of 15 studies that compared effects of training at low (5-20%) and high (20-45%) velocity loss thresholds. Our results show that for development of speed and power, low velocity loss thresholds are most appropriate. Regarding maximal strength, we found no significant differences between low and high thresholds. For strength endurance we did not have enough studies to make clear conclusions. The results of our work will be of great help at planning resistance training for development of speed, power, strength and strength endurance. Further research is needed to better understand differences in the effectiveness of different velocity loss thresholds depending on the exercise load.
Keywords: hitrost; moč; raziskave; šport; vadba